2017
DOI: 10.1242/dev.138164
|View full text |Cite|
|
Sign up to set email alerts
|

An essential role of CBL and CBL-B ubiquitin ligases in mammary stem cell maintenance

Abstract: The ubiquitin ligases CBL and CBL-B are negative regulators of tyrosine kinase signaling with established roles in the immune system. However, their physiological roles in epithelial tissues are unknown. Here, we used MMTV-Cre-mediated Cbl gene deletion on a Cbl-b null background, as well as a tamoxifen-inducible mammary stem cell (MaSC)-specific Cbl and Cbl-b double knockout (Cbl/Cbl-b DKO) using Lgr5-EGFP-IRES-CreERT2, to demonstrate a mammary epithelial cell-autonomous requirement of CBL and CBL-B in the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…4F). Organoid formation could be rescued by administration of an AKT inhibitor or rapamycin, indicating restoration of MaSC function (Mohapatra et al, 2017). More work is required to fully understand the role of mTOR signaling in MaSCs, but this initial report indicates that mTOR regulates a switch between MaSC self-renewal and differentiation, and that mTORC1 activity must be tightly regulated to prevent MaSC exhaustion.…”
Section: Mammary Stem Cellsmentioning
confidence: 98%
See 3 more Smart Citations
“…4F). Organoid formation could be rescued by administration of an AKT inhibitor or rapamycin, indicating restoration of MaSC function (Mohapatra et al, 2017). More work is required to fully understand the role of mTOR signaling in MaSCs, but this initial report indicates that mTOR regulates a switch between MaSC self-renewal and differentiation, and that mTORC1 activity must be tightly regulated to prevent MaSC exhaustion.…”
Section: Mammary Stem Cellsmentioning
confidence: 98%
“…However, despite our growing understanding of MaSCs, relatively little is known about mTOR in these cells. Recent work has demonstrated that deletion of the E3 ubiquitin ligases Cbl and Cblb impairs mouse mammary gland development in vivo, and abrogates MaSC function in vitro (Mohapatra et al, 2017). Cbl ubiquitin ligases limit receptor tyrosine kinase (RTK) signaling by mediating the proteosomal degradation of RTKs (Petrelli et al, 2002;Soubeyran et al, 2002).…”
Section: Mammary Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Along these lines, hematopoietic stem and progenitor cells from Cbl mutant mice showed increased PI3K/AKT, MAP kinase and STAT5 signaling, though there were differences in the signaling effects depending on the subpopulation analyzed (24). Third, two studies evaluated the effects of CBL mutants on a Cbl -/-/Cblb -/genetic background (35,41), which has the potential to augment or alter the signaling phenotype conferred by CBL mutant protein due to functional redundancy between Cbl and Cblb in mice (42)(43)(44). In patients with myeloid malignancies, CBLB mutations are uncommon and co-mutation of CBL and CBLB has not been described, suggesting that recurrent mutations in CBLB do not contribute significantly to oncogenesis.…”
Section: Discussionmentioning
confidence: 99%